Sulfur content in foods and beverages and its role in human and animal metabolism: A scoping review of recent studies - Dordevic, Dani; Capikova, Jana; Dordevic, Simona; Tremlová, Bohuslava; Gajdács, Márió; Kushkevych, Ivan (Heliyon, 2023)
Sulfur is a vital element that all living things require, being a component of proteins and other bio-organic substances. The various kinds and varieties of microbes in nature allow for the transformation of this element. It also should be emphasized that volatile sulfur compounds are typically present in food in trace amounts. Life cannot exist without sulfur, yet it also poses a potential health risk. The colon's sulfur metabolism, which is managed by eukaryotic cells, is much better understood than the S metabolism in gastrointestinal bacteria. Numerous additional microbial processes are anticipated to have an impact on the content and availability of sulfated compounds, as well as intestinal S metabolism. Hydrogen sulfide is the sulfur derivative that has attracted the most attention in relation to colonic health, but it is still unclear whether it is beneficial or harmful. Several lines of evidence suggest that sulfate-reducing bacteria or exogenous hydrogen sulfide may be the root cause of intestinal ailments, including inflammatory bowel diseases and colon cancer. Taurine serves a variety of biological and physiological purposes, including roles in inflammation and protection, additionally, low levels of taurine can be found in bodily fluids, and taurine is the primary sulfur component present in muscle tissue (serum and urine). The aim of this scoping review was to compile data from the most pertinent scientific works about S compounds' existence in food and their metabolic processes. The importance of S compounds in various food products and how these compounds can impact metabolic processes are both stressed in this paper.
Keywords: Gut microbiome; Hydrogen sulfide; Sulfate-reducing bacteria; Sulfur metabolism; Sulfur assimilation; Toxicity